The Relationship of Age and Weight for Glucose Level in the Vulcano Disaster Zona in Sleman Distric - Nugroho Susanto (Indonesian Journal of Global Health Research, 2023)
Body weight is factors related glucose level through increasing body weight. Diabetic disease addressed in high glucose blood through lifestyle role, hormones, physical activity. increasing of glucose associated with increased insulin dependent. Glucose level develop for diabetic complication through death. Study aims to know related age and body weight to glucose level in volcano area impacted. Study design with cross-sectional, were 112 sample required. Data age of subject, body weight and glucose were collected from January 2023th until June 2023th. Data of age were collected with medical record. Data weight were collected with “Xiaomi Mi Smart Scale” through medical record registered. Data glucose were collected with “Easy Touch GCU” based in medical record. Statistic data were analysed using descriptive with table of each variable. Data were analysed with chi-square test. Variable of age was no significant relationship between age and blood sugar levels, p = 0.126. The body weight was no significant relationship between body weight and blood sugar levels, p = 0.858. The factor of age and body weight no significant correlation with glucose level in volcano disaster are of Sleman District. Factor related glucose level maybe caused other factors such food consumption, physical activities.